A Crisis of Data? Transparency Practices and Infrastructures of Value in Data Broker Platforms. (2nd January 2023) - Zook, Matthew; Spangler, Ian
Abstract : Despite the prevalence of transparency discourses in economic life (e.g., postcrisis socioeconomic reforms), scholarship is just beginning to analyze how these discourses produce new relations between market actors in platform economies. In this article, we argue that in the context of financial markets and the political economy of data, transparency functions as a discursive construction that creates suitable conditions for the manufacture and extraction of data as an asset. First, we examine the role of transparency and opacity in various understandings of the 2007–2008 global financial crisis (GFC). In doing so we link the emergence of FinTech firms to a careful ex post facto reconstruction of the GFC as what we term a "crisis of data." Then, through problematizing the idea that transparent economic relations necessarily lead to greater accountability, equity, or public good, we argue that transparency is better understood as a relational practice that is continuously and contingently renegotiated. Taking up the example of debt data, we provide case studies of the data brokerage companies BlackRock and dv01 to analyze how transparency constitutes the material infrastructure of debt markets, which facilitates the construction of data assets for profitable circulation in a financialized political economy. We analyze our case studies with a focus on four transparency practices used to infuse data with value—building relationality, increasing granularity, managing directionality, and creating legibility.